HOTAIR: a potential metastatic, drug-resistant and prognostic regulator of breast cancer - Ganji Seeta Rama Raju; Eluri Pavitra; Sai Samyuktha Bandaru; Ganji Lakshmi Varaprasad; Ganji Purnachandra Nagaraju; Rama Rao Malla; Yun Suk Huh; Young-Kyu Han (Molecular Cancer, 2023)
Abstract HOX transcript antisense intergenic RNA (HOTAIR) is an oncogenic non-coding RNA whose expression is strongly correlated with the tumor grade and prognosis of a variety of carcinomas including breast cancer (BC). HOTAIR regulates various target genes via sponging and epigenetic mechanisms and controls various oncogenic cellular and signaling mechanisms including metastasis and drug resistance. In BC cells, HOTAIR expression is regulated by a variety of transcriptional and epigenetic mechanisms. In this review, we describe the regulatory mechanisms that govern HOTAIR expression during cancer development and explore how HOTAIR drives BC development, metastasis, and drug resistance. In the final section of this review, we focus on the role of HOTAIR in BC management, therapeutic treatment, and prognosis, highlighting its potential therapeutic applications.